The masterpieces of musical literature in the genre of tettings to music as an integral part of academic domra repertoire (Pedagogy of Higher and Secondary Education, 2009)
The article considers the outstanding examples of the word musical classics, which are constantly used in pedagogical and concert practice. Nowadays the genre of settings to music expressive means, to enrich the instrument's palette with new colors and images.
Keywords: setting to music; topical material; traditions; barocco; masteral instrumentalism; domra acdemuing; folklore; renaissance activities; melodic essence